THE INFLUENCE OF CONSUMER VALUE AND PERSPECTIVE OF VALUE TO INTENTION TO BUY THROUGH ATTITUDE TO ORGANIC PERSONAL CARE PRODUCT IN JAKARTA - Lina Lina (Universitas Trisakti, 2016)
The problem of this research was to identify the impact of consumer value and perspective of value to intention to buy through attitude, which is addressed to organic personal care product. The objective of this research was to analyze the effect of consumer value and perspective of value to intention to buy through attitude in organic personal care product. The methodology of this research was quantitative approach. Data were collected by 140 users of skin and hair care’s users at mall in Jakarta. The variable factors that used on this research are consumer value (health consciousness, environmental consciousness and appearance consciousness), perspective of value, attitude and intention to buy. Data analysis used Structural Equation Modelling (SEM). Finding and contribution in this research was environmentalconsciousness, appearance consciousness, and perspective of value have positive effect on attitude; and attitude has positive effect on intention to buy organic personal careproducts. Research limitation/implication in this research was the data only being collected in Jakarta. These findings here provide suggestion in order to increase intention to buy organic personal care, a product owner need to focus on ecological beauty, values and informational knowledge of organic benefit in their communication campaign